Involvement of the Histone Acetyltransferase AtHAC1 in the Regulation of Flowering Time via Repression of FLOWERING LOCUS C in Arabidopsis1[W][OA] - Deng, Weiwei; Liu, C.Y.; Deng, X.; Niu, L.; Cao, X.F. (American Society of Plant Biologists, 2007)
Histone acetylation is an important posttranslational modification correlated with gene activation. In Arabidopsis (Arabidopsis thaliana), the histone acetyltransferase AtHAC1 is homologous to animal p300/CREB (cAMP-responsive element-binding protein)-binding proteins, which are the main histone acetyltransferases participating in many physiological processes, including proliferation, differentiation, and apoptosis. The functions of p300/CREB-binding proteins in animals are well characterized, whereas little is known about the roles of AtHAC1 in developmental control in Arabidopsis. Lesions in AtHAC1 caused pleiotropic developmental defects, including delayed flowering, a shortened primary root, and partially reduced fertility. Analysis of the molecular basis of late flowering in hac1 mutants showed that the hac1 plants respond normally to day length, gibberellic acid treatment, and vernalization. Furthermore, the expression level of the flowering repressor FLOWERING LOCUS C (FLC) is increased in hac1 mutants, indicating that the late-flowering phenotype of hac1 mutants is mediated by FLC. Since histone acetylation is usually associated with the activation of gene expression, histone modifications of FLC chromatin are not affected by mutations in HAC1 and expression levels of all known autonomous pathway genes are unchanged in hac1 plants, we propose that HAC1 affects flowering time by epigenetic modification of factors upstream of FLC